2005
DOI: 10.1139/w05-022
|View full text |Cite
|
Sign up to set email alerts
|

Synergic interaction between pomegranate extract and antibiotics against Staphylococcus aureus

Abstract: We evaluated the interaction between Punica granatum (pomegranate) methanolic extract (PGME) and antibiotics against 30 clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive Staphylococcus aureus (MSSA). Susceptibility testing of the isolates to PGME and antibiotics was performed by the broth dilution method. Synergic activity was detected between PGME and the 5 antibiotics tested, chloramphenicol, gentamicin, ampicillin, tetracycline, and oxacillin, ranging from 38%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 18 publications
3
128
0
1
Order By: Relevance
“…In order to assess the effect of combinations of ethanolic extract and antibiotic, the MIC values for antibiotic were determined to be as a reference point for defining the interactions [26] . Synergistic effects resulting from the combination of antibiotics with various plant extracts have been studied earlier against MRSA or MSSA [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . From this study, ethanolic extract of E. elaterium fruits is very efficient in treating infectious diseases caused by MRSA and may also helpful for treating diseases caused by C. albicans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the effect of combinations of ethanolic extract and antibiotic, the MIC values for antibiotic were determined to be as a reference point for defining the interactions [26] . Synergistic effects resulting from the combination of antibiotics with various plant extracts have been studied earlier against MRSA or MSSA [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . From this study, ethanolic extract of E. elaterium fruits is very efficient in treating infectious diseases caused by MRSA and may also helpful for treating diseases caused by C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to light was avoided to prevent the loss of effective ingredients. Approximately [30][31][32][33][34][35][36][37][38][39][40] g of dried material were mixed thoroughly with magnetic stirrer in 200 mL of 80% ethanol at room temperature and the mixture left for 24 h. The insoluble materials were removed by centrifugation at 10 000 rpm for 10 min at 4 曟. Then, the extract was evaporated to dryness at 37 曟.…”
Section: Plant Extractionmentioning
confidence: 99%
“…Antitumour (Afaq et al, 2005;Lansky and Newman, 2007), antibacterial (Prashanth et al, 2001;Braga et al, 2005;Menezes et al, 2006;Aqil, Ahmad, 2007), antidiarrhoeal (Das et al, 1999;Mathabe et al, 2006), antifungal (Dutta et al, 1998Vasconcelos et al, 2003;Vasconcelos et al, 2006), antiulcer (Gharzouli et al, 1999), and antioxidant pharmacological properties have been reported for various extracts/constituents of different parts of this plant species. Recently, the antioxidant activity of P. granatum associated with its phytochemicals, such as, polyphenols, flavonoids, and anthocyanidins has gained importance (Faria et al, 2007;Guo et al, 2007;Kulkarni et al, 2007;Mirdehghan et al, 2007;Reddy et al, 2007;Rout, Banerjee, 2007;Sestili et al, 2007;Zaid et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…3 Punica granatum exhibits antibacterial action through bacteriostatic and bacteriocidal effect. 4 Research has also proved that the presence of ellagitannins and punicalagin is to be responsible for the antibacterial effect and the peel is often reported to be more effective than the seed extract. [5][6] However, studies related to antimicrobial activity of the P. granatum extract on most common human oral pathogenic microbes which persist in the oral cavity are scanty.…”
Section: Introductionmentioning
confidence: 99%